HUBUNGAN BUDAYA MEMBACA DENGAN KETERAMPILAN MENULIS CERITA PENDEK SISWA KELAS V SDN DUKUH MENANGGAL I/424 SURABAYA - Mega Puspita Sari; Sumiharsono, Rudy; Danang Prastyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reading culture is a positive routine activity that is good to do to train the brain to absorb all the best information received by someone in certain conditions and times. Short story writing skills are the ability to express ideas, thoughts, and feelings through written language in the form of fiction. This study was motivated by the problem related to the low frequency of reading of fifth grade students of SDN some students still seem less skilled in writing short stories. This study aims to determine the relationship between reading culture and short story writing skills of fifth grade students of SDN. This study uses a quantitative correlational method using an ex post facto research design. The population used in this study was the entire fifth grade of SDN Dukuh Menanggal I/424 Surabaya, totaling 61 students. The sample used was 30 students of class V-A as the experimental class and 31 students of class V-B as the actual class used in the study. Data collection techniques used questionnaires, tests, and documentation. Instrument testing used validity and reliability tests. Prerequisite testing used normality tests and homogeneity tests. Hypothesis testing in this study used the product moment correlation test. The calculated r was obtained at 0.489> r table 0.355, with a significance of 0.005 less than the significance level of 0.05, so Ho was rejected and H1 was accepted, meaning that the two variables were interrelated and the higher the reading culture of grade V students of SDN Dukuh Menanggal I/424 Surabaya, the higher the short story writing skills of grade V students of SDN.